THE PREDICTION POTENTIAL AREAS of CATCHING CAKALANG (Katsuwonus pelamis) BASED on CHLOROPHYLL-a DISTRIBUTION USING SATELLITE IMAGE NPP VIIRS IN WEST SUMATRA WATERS - Nur Audina; Usman '; Syaifuddin ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
The purpose of this studywas to determine the potential area for catchingcakalang (Katsuwonuspelamis) based on the distribution of chlorophyll-a satellite image of the NPP VIIRS in West Sumatra Waters by 2013. The methods used in this study are a survey method and spatial analysis. The results of this studysuggest that the location of the fishing ground cakalang by 2013 is at position 00 25 ' 48